Synthesis and characterization of 1-formyl-3-phenyl-5-aryl-2-pyrazolines - Sid, Assia; Lamara, Kaddour; Mokhtari, Mahieddine; Ziani, Nouara; Mosset, Paul (European Journal of Chemistry, 2011)
Reaction of chalcone derivatives 1-4 with hydrazine hydrate in presence of formic acid yielded 2-pyrazolines 5-8. Structures of these compounds have been elucidated by spectroscopic methods; IR, UV, 1H NMR, 13C NMR. Their purities were confirmed by elemental analyses.